2003
DOI: 10.1073/pnas.2134250100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic requirements for mycobacterial survival during infection

Abstract: Despite the importance of tuberculosis as a public health problem, we know relatively little about the molecular mechanisms used by the causative organism, Mycobacterium tuberculosis, to persist in the host. To define these mechanisms, we have mutated virtually every nonessential gene of M. tuberculosis and determined the effect disrupting each gene on the growth rate of this pathogen during infection. A total of 194 genes that are specifically required for mycobacterial growth in vivo were identified. The beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
1,185
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,203 publications
(1,262 citation statements)
references
References 43 publications
72
1,185
4
1
Order By: Relevance
“…Under the oxidative conditions during the persistent phase of the bacteria the CysM/CysO pathway appears to be the dominant route to cysteine [20,21]. The higher stability of both substrates, OPS compared to OAS [36] and CysO-SH compared to sulfide favour this pathway over the conventional route to cysteine in bacteria under oxidative stress.…”
Section: Cysteine Biosynthesis In Persistent M Tuberculosis May Requmentioning
confidence: 98%
See 1 more Smart Citation
“…Under the oxidative conditions during the persistent phase of the bacteria the CysM/CysO pathway appears to be the dominant route to cysteine [20,21]. The higher stability of both substrates, OPS compared to OAS [36] and CysO-SH compared to sulfide favour this pathway over the conventional route to cysteine in bacteria under oxidative stress.…”
Section: Cysteine Biosynthesis In Persistent M Tuberculosis May Requmentioning
confidence: 98%
“…Gene expression profiling of M. tuberculosis under oxidative stress showed up-regulation of both cysM and cysO [19] suggesting that this pathway may be of particular importance in the dormant phase of the pathogen. Further evidence for the essential role of this pathway in this pathogen comes from high density mutagenesis screens demonstrating that mutants carrying transposon insertions in cysM and/or cysO are attenuated in macrophages and in a mouse TB-model [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the proinflammatory state incited by active tuberculosis infection results in similarly high levels of Ado, and that Ado kinase is present in M. tuberculosis to take full advantage of this purine reservoir. While we may never definitively answer the question as to why M. tuberculosis has this activity, the necessity of Ado kinase to the Mycobacterium genus is evidenced by the presence of this gene in Mycobacterium leprae, which is widely considered to have a minimal genome, retaining only the genes that are necessary for survival [17].…”
Section: Introductionmentioning
confidence: 99%
“…A frequently cited method in this regard is that by Sassetti et al [29,30,31], in which gene arrays were created to rapidly identify transposon interrupted genes by the method called TraSH (transposon site hybridization). An 'essential gene list' was compiled based on growth of M. tuberculosis H37Rv mutants on 7H10 agar containing OADC enrichment [30].…”
Section: Array Technologies Accelerate Screening Of Mycobacteria Mutantsmentioning
confidence: 99%
“…Establishing different in vitro culture conditions to represent active and stationary phase, Kumar et al [53] have shown that genes within mce operons 1-4 are expressed in stationary phase (such as in standing cultures), while one or more mce genes are expressed during active growth. Only mce1 and mce4 of M. tuberculosis have been deemed essential for survival [31]. Kumar et al [53] proposed that the biological functions and evolution of these clusters indicate a fundamental role in transport (for nutrients, metabolites, and extrusion of toxic molecules in saprophytic organisms via the Ttg2C domain), which have then been adapted for cell entry functions by pathogenic bacteria via the mce domain.…”
Section: Mcementioning
confidence: 99%